ANALISA PERBANDINGAN BIAYA DAN WAKTU METODE KOSTRUKSI TOP-DOWN DAN BOTTOM-UP PADA PEKERJAAN BASEMENT GEDUNG TENTREM SEMARANG - Sabdo Manggolo; Antonius; Kartono Wibowo (Jurnal Teknik Sipil dan Arsitektur, 2023)
Tentrem Semarang Building is one of the tallest buildings in Semarang with 4 basement floors and 17 top floors. The construction of basements in high-rise buildings is currently being carried out a lot, one of the factors is due to the limited land to be built, in general, the construction of basements is used for parking lots. The basement to be built has different depths and conditions, so it takes the right method according to the conditions in the field. There are 2 methods for implementing basement construction, namely bottom-up and top-down. In the basement structure work of the existing Tentrem Semarang Building construction project, the basement construction used the bottom-up construction method. In this study, the method will be modified using the top-down construction method. Information regarding work methods, worker productivity was obtained by interviewing field supervisors from the owner, interviews with supervisors from the main contractor and direct field observations. Calculation of costs and time is carried out by analyzing the capacity and productivity of labor and heavy equipment, comparing the normal time with the time after changes in construction methods. The results of the modification of the construction method using the top-down construction method for the basement structure of the Tentrem Semarang Building project took 510 days to complete and cost IDR 205,059,861,826. Whereas for the bottom-up method it takes 685 days with a total cost of IDR 253,609,405,225. The application of the Top-Down method to the implementation of the basement structure of the Tentrem Semarang building project is more effective and efficient than the implementation of the Bottom-Up method and produces a time effectiveness value of 25.55% and a cost efficiency of 19.14% compared to the Bottom-Up method